STUDENTS’ RESPONSES TOWARDS E-LEARNING SCHOOLOGY CONTENT ON CREATIVE WRITING LEARNING DURING THE COVID-19 PANDEMIC - Ernalida Ernalida; Santi Oktarina; Ansori Ansori (English Review: Journal of English Education, 2021)
The era of the COVID-19 pandemic brought major changes in the world of education, not only in Indonesia, but in the world. Almost all countries feel the same way. The learning system has switched from an offline/face-to-face to an online system. This world disaster has made many new applications appear or the famous applications that support online learning. One of them is Indonesian learning which requires learning technology, especially writing skills; creative writing. Writing skills in high school are needed. There are many types of creative writing that must be mastered by students, such as writing biographies, writing short stories, writing poetry, and so on. Moreover, in the 2013 curriculum, Indonesian language learning is text-based which directs students to be able to produce text-based writings. The purpose of this study was to determine the practicality of the content of E-Learning Schoology in learning creative writing in high schools in Palembang city in terms of teachers. This research is research and development research. The object of research is the 10th grade Indonesian at SMA Palembang. The method used is the Delpi method. Data collection techniques are questionnaires and FGDs. Data were analyzed quantitatively and qualitatively. Based on the results of research and discussion, it can be concluded as follows. First, the E-Learning Schoology content for creative writing learning has been practically used based on the small group test which was participated by 10 students. This practicality can be seen from the assessments given by students on aspects of material, language, content presentation, and E-Learning which show a very decent value. Mean value which was above 4.25. Second, the students stated that the content developed has advantages such as, interesting, motivating, complete material, easy to use, inspiring, provides many learning experiences, the language is easy to understand, the features used are interesting and make it easier to learn. Third, this content has weaknesses, but these weaknesses occured because of the lack of understanding of students in operating this e-learning.